Route optimization scenario of a new scheme based on nested mobile network - Senan, Shayma; Hassan Abdalla Hashim, Aisha; Saeed, Rashid Abdelhaleem; Hameed, Shihab A.; Zeki, Akram M.; Daoud, Jamal Ibrahim (2012)
With the rapid growth of wireless technologies and increasing number of mobile digital devices, mobility has been an important element on the Internet. NEMO Basic Support, designed by the Internet Engineering Task Force (IETF) to provide network mobility, is not efficient to offer low latency handoff in the case of nested mobile networks because it produces a long transfer delay and excessively large packet sizes due to non-optimal routes and multiple encapsulations. This paper presents a route optimization scenario for nested mobile network using hierarchical structure with Binding Update Tree (BUT). This scheme should reduce packet overhead, handoff latency, packet transmission delay, and achieve optimal routing.